2022
DOI: 10.3390/brainsci12020135
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Stress Induced by Intraperitoneal Injection of LPS Increases Phoenixin Expression and Activity in Distinct Rat Brain Nuclei

Abstract: Due to phoenixin’s role in restraint stress and glucocorticoid stress, as well as its recently shown effects on the inflammasome, we aimed to investigate the effects of lipopolysaccharide (LPS)-induced inflammatory stress on the activity of brain nuclei-expressing phoenixin. Male Sprague Dawley rats (n = 6/group) were intraperitoneally injected with either LPS or control (saline). Brains were processed for c-Fos and phoenixin immunohistochemistry and the resulting slides were evaluated using ImageJ software. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…As shown previously by our research group, both restraint stress (Friedrich et al, 2020) and immunological LPS stress (Friedrich et al, 2022) altered central phoenixin immunoreactivity. Restraint stress simulated emotional stress and caused an increase in activity and phoenixin density in several nuclei, namely the RPa, mNTS and DMN (Friedrich et al, 2020).…”
Section: Implications In Stress and Anxietysupporting
confidence: 87%
“…As shown previously by our research group, both restraint stress (Friedrich et al, 2020) and immunological LPS stress (Friedrich et al, 2022) altered central phoenixin immunoreactivity. Restraint stress simulated emotional stress and caused an increase in activity and phoenixin density in several nuclei, namely the RPa, mNTS and DMN (Friedrich et al, 2020).…”
Section: Implications In Stress and Anxietysupporting
confidence: 87%
“…Although IP injections are easier and more convenient, IV injections allow for more consistent levels of LPS in the blood as well as faster induction of an immune response and neuroinflammation ( 33 ). Acute LPS injections in rats have shown to induce significant systemic and central inflammation, including different regions of the brain, as early as 2 hours after inoculation ( 34 , 35 ). In human studies, the typical route of LPS injection is IV as well.…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiological recordings from brain slices demonstrated that phoenixin-14 reduced the interictal-like events in the entorhinal cortex and hippocampus ( Kalkan et al, 2021 ), suggesting a potential role of phoenixin-14 in epileptiform activity. Recent study demonstrated that inflammatory stress induced by LPS up-regulated phoenixin expression and activity in the specific brain nuclei of SD Rats, indicating that several stressors could activate phoenixin signaling ( Friedrich et al, 2022 ).…”
Section: Function Of Phoenixinmentioning
confidence: 99%